Những yếu tố ảnh hưởng đến ý định sử dụng tiền di động của khách hàng tại huyện Di Linh, tỉnh Lâm Đồng - Hoàng Việt, Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The aim of the current research is to investigate the influence of perceived ease of use, perceived usefulness, facilitating conditions on attitudes towards using mobile money, and intention to use mobile money among customers living in Di Linh district, Lam Dong province, Vietnam. Structural equation modeling (SEM) using SMART-PLS was used to analyze the structural relationships between the variables. Results indicate that perceived ease of use, perceived usefulness, and facilitating conditions are positively associated with the intention to use mobile money. Attitude towards using mobile money is found to partly mediate the relationship between perceived ease of use, facilitating conditions, and intention to use mobile money. Based on this result, this research helps telecommunication companies to build strategies more purposely and effectively to attract more customers to use mobile money and assist in expediting the digital transformation process in the remote, rural, and island regions of the country. Further studies could apply this model to test the intention to use mobile money among customers in different regions of Vietnam.